International Classification of Functioning, Disability, and Health-based rehabilitation program promotes activity and participation of post-stroke patients - Wong, Mabel Ngai-Kiu; Cheung, Mike Kwun-Ting; Ng, Yuk-Mun; Yuan, Huan-Ling; Lam, Bess Yin-Hung; Fu, Siu Ngor; Chan, Chetwyn Che Hin (Frontiers in Neurology, 2023)
The International Classification of Functioning, Disability, and Health (ICF) model has been applied in post-stroke rehabilitation, yet limited studies explored its clinical application on enhancing patients' Activity and Participation (ICF-A&P) level.Purpose: This study gathered evidence of the effects of an ICF-based post-stroke rehabilitation program (ICF-PSRP) in enhancing community reintegration in terms of ICF-A&P of post-stroke patients.Methods: Fifty-two post-stroke patients completed an 8-to-12-week multidisciplinary ICF-PSRP after setting personal treatment goals in an outpatient community rehabilitation center. Intake and pre-discharge assessments were administered for primary outcomes of Body function (ICF-BF; e.g., muscle strength) and ICF-A&P (e.g., mobility), and secondary outcomes of perceived improvements in ability (e.g., goal attainment and quality of life).Results: There were significantly higher levels in the ICF-BF and ICF-A&P domains, except cognitive function under the ICF-BF. Improvements in the primary outcomes predicted corresponding secondary outcomes. Firstly, expressive and receptive functions (ICP-BF) were mediated by the everyday language (ICF-A&P) which predicted patients' satisfaction with the language-related quality of life. Secondly, upper extremity function (ICP-BF) was mediated by the lower extremity mobility (ICF-A&P) predicting work and productivity-related quality of life. Content analyses showed that combined ICF-BF and ICF-A&P contents throughout the ICF-PSRP contributed to the positive treatment effects.The ICF-PSRP was effective in promoting body function, and activity and participation levels of post-stroke patients. Positive treatment effects are characterized by goal-setting process, cross-domain content design, and community-setting delivery.